2017
DOI: 10.1371/journal.ppat.1006184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the T Cell Response to Zika Virus and Identification of a Novel CD8+ T Cell Epitope in Immunocompetent Mice

Abstract: Zika virus (ZIKV) is an emerging arbovirus of the Flaviviridae family. Although ZIKV infection is typically mild and self-limiting in healthy adults, infection has been associated with neurological symptoms such as Guillain-Barré syndrome, and a causal link has been established between fetal microcephaly and ZIKV infection during pregnancy. These risks, and the magnitude of the ongoing ZIKV pandemic, have created an urgent need for the development of animal models to study the immune response to ZIKV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
140
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(155 citation statements)
references
References 49 publications
12
140
0
3
Order By: Relevance
“…Of these six peptides (Table 1), the epitope E 4 -12 induced the highest IFN-␥-producing cells (i.e., 3 to 4% IFN-␥ ϩ CD8 ϩ cells after ZIKV infection), suggesting the immunodominance of E 4 -12 epitope among positive peptides we identified. This finding was also consistent with Pardy's report that the E 4 -12 epitope was recognized by a majority of responding cells during ZIKV infection (9). Two peptides derived from the E protein (E 4 -12 and E 310 -317 ) and one from NS2A (NS2A 91-98 ) of our virus strain are consistent with a recent report (5).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Of these six peptides (Table 1), the epitope E 4 -12 induced the highest IFN-␥-producing cells (i.e., 3 to 4% IFN-␥ ϩ CD8 ϩ cells after ZIKV infection), suggesting the immunodominance of E 4 -12 epitope among positive peptides we identified. This finding was also consistent with Pardy's report that the E 4 -12 epitope was recognized by a majority of responding cells during ZIKV infection (9). Two peptides derived from the E protein (E 4 -12 and E 310 -317 ) and one from NS2A (NS2A 91-98 ) of our virus strain are consistent with a recent report (5).…”
Section: Resultssupporting
confidence: 93%
“…These models are sufficient for characterizing infection and the pathogenesis of the virus because a clear infection phenotype is observed, but they are unable to provide a comprehensive and accurate understanding of the natural immune response to ZIKV infection. Recently, two reports indicated that ZIKV can infect WT mice and activate CD8 ϩ T cells (8,9). Our studies extended these findings by characterizing the immune response to ZIKV more comprehensively in the key peripheral organs of WT adult mice.…”
Section: Cd8 ϩ T Cell Immune Response In Zika Virus Infectionsupporting
confidence: 68%
See 2 more Smart Citations
“…Indeed, several works have already investigated the recognition of Zika virus by T cells (57,58), and others have shown that Zika virus infection can induce type I IFNs and downstream interferon-stimulated genes (ISGs). Zika virus infection of human skin fibroblasts induced the transcription of Toll-like receptor 3 (TLR3), RIGI, and MDA5, as well as other ISGs, such as OAS2, ISG15, and MX1 (59).…”
Section: Discussionmentioning
confidence: 99%